Collaborative story production with bereaved family carers of people who died in advanced age. (20th August 2018) - Moeke-Maxwell, Tess Huia; Wiles, Janine; Black, Stella; Williams, Lisa; Gott, Merryn
Abstract : Purpose: Is collaborative story production (CSP) a useful method to collaborate with bereaved families to record their reflections on the end of life circumstances and care of people of advanced age? The paper aims to discuss this issue. Design/methodology/approach: Drawing from Te Pākeketanga, a bicultural study involving 58 bereaved Māori and non-Māori families on behalf of 52 older relatives, the authors describe the CSP method. Researchers and participants co-created personalised written stories about the older person and their end of life experiences, supported with photographs of family, friends and memorabilia. The authors aimed to uplift the status of the older person and their family by tangibly reflecting the significance and magnitude of what had been shared and to strengthen the research analysis. Findings: CSP supported member checking, promoted a robust understanding of participants' narratives and increased the trustworthiness of data and strengthened the Kaupapa Māori and social constructivist analysis. However, some participants experienced difficulty revisiting painful memories when reading their story. CSP took longer than anticipated, was labour intensive and required a highly skilled and resourced team to ensure participants benefitted. Originality/value: Using the CSP method with a bicultural cohort of bereaved families who had provided care to someone over the age of 80 was very helpful in assisting the researchers to gather narrative information and present it back to participants in a story format for their comment and feedback. The method contributed a useful way to partner with bereaved family caregivers following the death of an older family member. The authors needed a way to record the participants' narratives of the older person's end of life circumstances and end of life care experiences. This was very important, particularly for grieving families and indigenous families who may have felt vulnerable engaging with research, and with the research processes. The approach provided a helpful and non-intrusive member-checking process. The unique bicultural study approach deliberately utilised the CSP method to assist the researchers to work safely with bereaved families as the participants reflected upon and explored not only the end of life circumstances of the older person, but they also focused on the "death" and their own bereavement experiences. CSP also provided a helpful member-checking method; the authors were working with highly sensitive information and wanted to ensure that the authors as researchers understood and interpreted the families' narrative data correctly, according to their perspectives.